Upaya Meningkatkan Hasil Belajar Sistem Operasi Open Source Komputer Multi Media Melalui Model Pembelajaran Diskusi dan Eksperimen - YAYAH NUR ALIYAH (Fakultas Ekonomi Universitas Negeri Jakarta, 2016)
ABSTRACT The research was purposed to find out the effectiveness of discussion and experiment models are able to improve study result of students in operation system computer open source of multimedia learning in X Multimedia in SMKN 48 at Academic Year 2014/2015. The reasearch was conducted on July-Desember 2014. The method of the research was Action Research (PTK) which was conducted in two cycles. Discussion and Experiment were used as learning cycle model. A cycle consisted in three times of meetings and in the third meeting was done Post test. The indicators have been achieved by the result of research. As the expectation, in the second cycle, namely the number of students got the highest points was 97,45% of 32 Students and average value was 80,79%. The completeness of students was achieved and students did negative activity was not more than 35 % but only 1,55%. In the second cycle can be said that achievements of students learning have improved by using discussion and experiment learning model. Giving special attention to Less-achievement and Passive Students of work at monitoring group discussion and experiment. In conclusion, discussion and experiment are able to improve students’ study result in operation system computer open source of multimedia learning if it was implemented appropriately in X Multimedia in SMKN 48 Jakarta. Keywords : Discussion, Experiment, and Operation system open source